Utilization of the Geographic Information System Application in Making Sales Decisions at the Al2 Motor Store, Gorontalo Regency - Yusuf, Susanto Ali; Hamin, Udin; Rachman, Ellys (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objectives of this research are: (1) to describe the availability of resources in decision making at AL 2 Shop, Gorontalo Regency, (2) to describe the factors inhibiting the use of the Geographic Information System application in decision making at AL 2 Shop, Gorontalo Regency. This research is qualitative research that is descriptive analysis using a phenomenological approach. The research results show: First, the availability of resources in decision making at AL Shop 2, Gorontalo Regency, including: (a) The computer hardware used includes labtops, chromebooks, printers and barcode scanners. (b) in terms of software, in utilizing this application, the Gorontalo Regency AL Motor Shop pays attention to several things, including: GIS, office, windows, (c) in terms of data and information, GIS has two interconnected data models, namely spatial data and nonspatial data.